Becoming Centaur : Eighteenth-Century Masculinity and English Horsemanship - Mattfeld, Monica, 1982- (Book collections on Project MUSE., 2017)
"Explores the history of horse-human relationships over the long eighteenth century, and how these relationships in turn influenced performances of gender. Examines the agential influence of horses in their riders' lives, horses on stage and the early circus, and the politicization of human-animal being"--Provided by publisher